Analisis Pengaruh Budaya Organisasi Terhadap Kinerja Keuangan Pada KSP Balo’ta Tana Toraja - Aprilyanita Lambe Tandungan; Dina Ramba; Jemi Pabisangan Tahirs (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to analyze and describe the influence exerted by Organizational Culture on Financial Performance in KSP Balo’ta Tana Toraja. This type of research used is quantitative research. Data were obtained by conducting direct interviews, observations, and documentation at KSP Balo’ta by optaining primary data obtained by researches by conducting direct interviews with informants and secondary data in the form of data that has been documented at KSP Balo’ta such as a brief history, cooperative location, and organizational structure. The data analysis technique used in this study is simple linear regression analysis which is then processed using the SPSS software aplication version 16.0. The data used in this study is primary data using a questionnaire, the number of respondents usedin this study is 53 respondents by taking the data source from employees at KSP Balo’ta. Then there are several analytical methods used, namely the validity test,reliability test,simple regression test, p plot of regression test,test T and the coefficient of determination. This study shows that Organizational Culture has a positive and significant effect on financial performance.